Abnormal coronary anatomy in patients with atrial switch: a predictor of serious cardiac adverse event?. (25th November 2020) - Perreux, Y.P; Chaix, M.C; Fongeon, F.P; Di Filippo, S; Boussel, L; Khairy, P; Bessiere, F
Abstract: Introduction: Sudden death and heart failure are severe long-term complications after atrial switch for D-transposition of the great arteries (D-TGA). Mechanisms and factors of long-term complications are poorly known. Right ventricle ischemia may be involved in these complications. Since coronary malformations are present in about 30% of D-TGA, we aimed to look for an association between these complications and the presence of coronary anomalies. Methods: The study is an observational international study in two tertiary centers. Adults with history of atrial switch and severe rhythmic or hemodynamic complications, history of heart transplantation or cardiovascular death were included. Patients under 18 years old and/or with corrected transposition of great arteries were excluded. A χ 2 test was used to compare the proportion of coronary anomalies in this cohort to the one from population of D-TGA reported in previous studies. Results: Forty-two patients were included: 11 women (26.2%) and mean age at the time of the study was 43.3±6.4 years. Eight patients (19.0%) died at a mean age 41.3±9.0 years. No ablation for ventricular tachycardia was reported while 15 (35.7%) patients underwent ablation for a SVT (supraventricular tachycardia). Thirty three patients (78.6%) suffered from heart failure and/or severe right ventricle dysfunction and 4 patients (9.5%) were transplanted at a mean age of 29.3±8.3 years. Ten (23.8%) patients suffered from both arrhythmic events and heart failure. Twelve patients (28, 6%) had abnormal coronary anatomy. The χ 2 test showed no significant difference of coronary anatomy between our population and a pooled population of 647 D-TGA from previous studies (28.7%, p=0.9804). By multivariate analysis, severe pulmonary hypertension and severe tricuspid regurgitation were significantly associated with cardiovascular death and/or heart transplantation (respectively: p=0.0323, OR= 2.5, and p=0.0494, OR= 4.0). SVT ablation tended to be associated to survival (p=0.0928 with OR= 2.2). Conclusions: No difference of coronary anomalies ratio in complicated Mustard or Senning patients was seen in comparison with the coronary anomalies ratio of all D-TGA. These results plead against a role of abnormal coronary anatomy in right ventricle dysfunction. Ischemia may be more related with the alteration of micro vascularization and a mismatch between oxygen needs and supply. Funding Acknowledgement: Type of funding source: None